Peningkatan Perilaku Anti Korupsi Melalui Metode Story Telling: Penelitian Tindakan TK B Az Zahra, Kebayoran Baru, Jakarta Selatan, Tahun 2016 - Lestari, Dwi Puji (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2018)
The purpose of this research was to determinate the proccess of implementation of story telling metode to increase behavior of anti-corruption in Group B Az Zahra Kebayoran Baru South of Jakarta. This research is an action research which refers to the model of a classroom Action Research Kemmis and Mc. Taggart. The subject of this research are children in Group B Az Zahra Kebayoran Baru South of Jakarta there are 16 children, who consist of 6 girls and 10 boys. The steps of this research : 1) Planing (2) Action (3) Observation (4) Reflection. Data analysis used quantitative and qualitative. Data analysis qualitative used Miles and Hubberman model. This research do in two cycles, there are cycle I and II. The end result of the overall analysis of the data is the percentage in 88,05% cycles II which showed from pre-cycle is 41,23% up to cycles I 72,32%